Addressing stunting reduction: The role of midwives and nurses - Rithpho, Pratuma; Klankajhon, Sirikanok; Buakhai, Pantipa (Pediomaternal Nursing Journal, 2025)
Stunting remains a significant public health concern, particularly in low- and middle-income countries, where it affects millions of children due to chronic malnutrition. This editorial highlights the critical role of midwives and nurses in addressing stunting through maternal education, nutritional support, and healthcare interventions. Midwives play a key role in antenatal care, maternal nutrition counseling, and breastfeeding promotion, while nurses contribute through growth monitoring, nutritional counseling, immunization, and community outreach. Strengthening healthcare professionals' capacity, improving infrastructure, and fostering interdisciplinary collaboration are essential to reducing stunting. Empowerment, family involvement, and social movements can further enhance public health outcomes. Keywords: child nutrition; maternal health; midwives; nurses; public health interventions; stunting